Assisting in the physical examination - Mosby Lifeline ([St. Louis, MO] : Mosby Lifeline, 1994)
(Producer) Included in this video: patient history/review, methods of physical examination, assisting with the physical examination, positioning and draping patients, equipment and other instruments used in special examinations, care of equipmentafter use, care of obtained specimens
Keywords: Physical Examination -- methods